A multicriterial Analysis of National Competitiveness: Evidences for a Resilient Economy - Sima, Violeta; Gheorghe, Ileana Georgiana (Industrija, 2017)
This article is structured in three parts, as follows: In the first part, we summarized the different approaches of national competitiveness in the literature on the economic performance assessment, using specific indexes: Global Competitiveness Index (GCI), Ecological Performance Index (EPI), and Human Development Index (HDI), highlighting their advantages and limitations. These variables were analyzed ante-crisis and ex-crisis, assuming that the economic recession could generate some effects. Data sources are presented at the beginning of the ‘Results and discussion’ paragraph. Considering the diversity of the issues and the inhomogeneity of data describing those issues, GDP was used along with the four composite indicators: GCI, EPI, HDI, and Economic Resilience Index (ERI). The third part presents the main findings and their implications. Thus, a downward trend of the evolution of Romania’s economic resilience index during 2008-2014 was observed. This decline appears to be due largely to the decrease in Social development sub-index and in Governance sub-index. The low level of the Romanian economy resilience is mainly explained by the low level of competitiveness and productivity of production factors. The obtained outcomes suggest that in addition to national competitiveness assessing, ERI evaluation is important because it can reveal the hidden sources of vulnerability of the economy to external shocks.